The Dynamics, energetics and selectivity of water chain-containing aquapores created by the self-assembly of aquafoldamer molecules. Issue 43 (18th September 2015) - Ma, Wenliang; Wang, Chunquan; Li, Juntong; Zhang, Kun; Lu, Yu-Jing; Huo, Yanping; Zeng, Huaqiang
Abstract : Self-assembled hollow tubular aquapores were found to be stable, very dynamic yet highly selective toward recognition of water molecules. Abstract : Through a series of crystallographic snapshots of water chain-containing aquapores formed from numerous one-dimensionally aligned aquafoldamer molecules2, we demonstrated here (1) a preferential recognition of the water molecules over methanol molecules by the assembled cavity-containing aquapores with a selectivity factor of at least 17.7, (2) the dynamic nature of the water chains and the aquapores in response to varying external stimuli that exert the most influential impact on the aromatic π–π stacking in the aquapores and (3) the aquapores undergo a significant rearrangement in order to accommodate water, rather than methanol, molecules.